Sandy soil contamination with coal fly ash by long term leaching test - Lange, Camila Neves; Boscov, Maria Eugênia Gimenez; Carmargo, Iara Maria Carneiro (Águas Subterrâneas, 2011)
Toxic elements can cause impact on soil environmental quality and represent risks to human life. Coal ashes, considered as a source of toxic elements, are commonly disposed of inadequately on the soil surface around thermoelectric plants. The aim of this study was to evaluate the contamination of a clayey sand by As, Cd, Mo Pb and Zn from coal fly ash of Figueira Power Plant. Experiments with coal fly ash added on soils columns were carried out to simulate contamination by acid leaching. Results indicate that the soil was mainly contaminated by As, which exceeded the intervention value for maximum protection area (APmax) established by the Environmental Protection Agency of the State of São Paulo (CETESB).